PENGARUHPENGAWASAN, STRUKTUR ORGANISASI, INTEGRASI DAN INOVASI TERHADAP KEUNGGULAN BERSAING UNIVERSITAS MUHAMMADIYAH MAKASSAR - BAHARUDDIN, BAHARUDDIN (PPs UNJ, 2015)
This study aimed to determine the effect of controlling, organization structure, integration, innovation on competitive advantage lecturers. This research used quantitative approach with survey method and structural equation model (SEM).The data of 5 variables were analysed by path analysis techniques. Research result showed that: (1) there is a direct positive effect of the innovation on the competitive advantage lecturers, (2) there is a direct positive effect of the integration of the competitive advantage lecturers, (3) there is a direct positive effect on the integration on the innovation, (4) there is a direct positive effect of the organizational structure on the competitive advantage lecturers, (5) there is a direct positive effect of the organizational structure on the innovation, (6) there is a direct positive effect of the organizational structure on the integration, (7) there is a direct positive effect of the controlling the competitive advantage lecturers, (8) there is a direct positive effect of the integration on the competitive advantage lecturer, (8) there is a direct positive effect of the controlling on the innovation, (9) there is a direct positive effect on the controlling of the integration, (10) there is a direct positive effect of the controlling on the competitive advantage lecturers. The results of the analysis descriptive competitive advantage lecturers very high and controlling, organization structure, innovation to make continouns improvement.